First Report of Chinese Cabbage Wilt Caused by Plectosphaerella cucumerina in Inner Mongolia of China - Gao, Jing; Zhang, Yuanyuan; Liu, Xiangping; Liu, Yan; Kang, Liru; Jun, Zhang; Lian, Yong; Yang, Zhigang; Wang, Yong (Plant disease, 2022)
Chinese cabbage [Brassica rapa L. subsp. pekinensis (Lour.) Hanelt] has been grown commercially for many decades in Huade County, Inner Mongolia. In 2018 and 2019, an unusual stem and leaf wilt disease with an average disease incidence of approximately 3% was observed. Diseased plants with spindle-shaped stem lesions were collected and small pieces (0.3 × 0.3 cm) of the diseased tissues were cut from the margins of stem lesions, surface sterilized with 75% alcohol for 3 to 5 s, 0.1% NaClO for 2 to 3 min, and washed three times with sterilized water. The treated tissues were placed on 1.5% (w/v) water agar plates and incubated at 25°C for 3 days. The mycelia were cut and transferred onto potato dextrose agar (PDA) for culture purification. Three isolates with similar morphology were obtained and named as BC-2, BC3-2 and BG2. To confirm their pathogenicity, Chinese cabbage (cv. Chunqiuhuang) seed was planted into plugs. After 30 days, the fibrous roots were wounded with a fruit knife and root-dipped in the conidium suspension (1 × 106 conidia/ml) for 20 min. Inoculated seedlings were transplanted in pots (30 × 25 cm) with sterilized nursery soil, with one seeding per pot. The roots of control plants were also wounded and dipped in sterilized water. Five seedlings were inoculated with each isolate and the experiment was repeated three times. Treated seedlings were maintained in a greenhouse at 25 to 28°C under a 12-h photoperiod. Chlorosis and wilting were observed approximately 4 weeks after inoculation, and the outer layer of leaves of the inoculated seedlings developed discoloration and wilted symptoms after 50 days. The symptoms induced by all three isolates were the same as the symptoms observed in the field, whereas no symptoms developed on the control plants. To confirm the Koch's postulates, the fungus was successfully re-isolated from the infected leaves and had similar growth and morphology as the original isolates. The three isolates were cultured for both morphology and molecular identification. The 14-day-old colonies on PDA were buff or salmon pink with few aerial hyphae, and slimy surfaces. Aerial hyphae were sparse with simple or branched conidiophores. Conidia were ellipsoidal, hyaline, surface smooth, septate or aseptate, and (4.0 to 9.7 μm × 2.0 to 3.9 μm). Such characteristics are typical of Plectosphaerella spp. (Palm et al. 1995). For molecular identification, the internal transcribed spacer (ITS) region of rDNA was amplified using the primer pair ITS1/ITS4 (White et al. 1990), and the products were directly sequenced. BLAST analysis showed that the sequences of Isolates BC-2 (511 bp out of 515 bp), BC3-2 (512 bp out of 516 bp) and BG2 (503 bp out of 505 bp) showed 99% identity to an isolate of P. cucumerina (acc. no. KT826571.1) from Bottle gourd [Lagenaria siceraria (Molina) Standl.] (Yan et al. 2016). The sequences of Isolates BC-2, BC3-2 and BG2 were deposited in GenBank (acc. nos. MW320463, MW320462 and MW320464). Although P. cucumerina was reported causing root rot of cabbage (B. oleracea) in Gansu, China (Li et al. 2017), to our knowledge, this is the first report of P. cucumerina causing Chinese cabbage wilt in Inner Mongolia, China. The presence of the disease could cause significant economic losses in Chinese cabbage production. For this reason, strategies for the management and control of this disease should be implemented.